Multirate digital signal processing multirate systems, filter banks, wavelets - Fliege, N.J (John Wiley & Sons, 1994)
Provides a thorough and accessible introduction to the fast-growing area of multirate digital signal processing covering both the fundamental theory and the practical applications. The key characteristic of multirate algorithms is their high computational efficiency, and hence their increasing implementation in a range of applications from digital audio broadcasting to multi-carrier data transmission and subband speech coding